PERSPECTIVES OF APPLICATION OF TECHNOLOGICAL PROCESSES IN PRODUCTION OF METAL CORD - A. I. Gordienko; V. V. Krylov-Olefirenko (Литьë и металлургия, 2009)
The results on investigations on the problems of metal cord production are given. The matters connected with generation of single-phase corrosion-resistant brass covering, breakages at laying and plasticity after low-temperature processing are considered.